THE EFFECT THYROXINE HORMONE (T4) DOSES AND PHASE IMMERSION ON GROWTH AND SURVIVAL RATE OF RIVER CATFISH LARVAE (Hemibagrus nemurus) - Fatihatir Rahmi; Nuraini Nuraini; Nur Asiah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This research was conducted on September 12, 2020 - October 12, 2020, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to determine the effect ofthyroxine hormone and the optimal dose and immersion phaseon growth and survival rate of river catfish larvae (Hemibagrus nemurus). The method used was a Completely Randomized Design Factorial with 2 factors. The first factor was the dose of thyroxine hormone with 4 levels; 0 mg/L (D0), 0,1 mg/L (D1), 0,3 mg/L (D2), and 0,5 mg/L (D3). The second factor was the immersion phase with 2 levels of immersion egg (FL) and immersion larvae (FL).The larvae were cultured preserved in jars for 30 days with 2 fish/L density. The results showed that the use of different doses and immersion phase of thyroxine hormone effected on absolute weight, absolute length, specific growth and survival rate of river catfish larvae. Treatment dose 0,3 mg /L and immersion larvae (D2FL) with the result of absolute weight growth of 2.08 grams, absolute length 5.02 cm, specific growth rate of 20.94 % and survival rate of 92.00 %. The water quality parameters during the study were optimal for river catfish larvae with temperature 27.8-28.9 oC, pH 5.9-6.9 and dissolved oxygen 3.5-6.8 mg/L.Keywords :Doses, Immersion phase, Thyroxine hormone,Hemibagrus nemurus